Wujud Kearifan Lokal dalam Bentuk dan Fungsi Folklor Lisan Banyumas - Bambang Lelono; Roch Widjatini (Faculty of Humanities, Universitas Jenderal Soedirman, 2019)
The purpose of this research is for inventory the forms of verbal folklores in Banyumas. Banyumas known by various predicates, one of which is the uniqueness of the language and culture. Banyumas dialect called ngapak language that are characteristic of the Banyumas. There is a typical expression of the living Banyumas although not as strong as Banyumas dialect, proverbs form of expression is “ora ilok”. The are more folklore, the origin of which Baturaden. This is a form of local wisdom in Banyumas verbal folklore. Method used in this research is ethnography method. The result of analysis said that Ngapak banyumas or dialects used in every day communication among people in Banyumas informal situations. As for the phrase “ora ilok” inBanyumas is a tradition that should be preserved because it contains the teachings of morality. Folklore about the origin Baturaden now a tourist spot as one of nature's assets in Banyumas district area.